The Incidence and Clinical Relevance of Coronary Artery Anomalies Detected on Multidetector Computed Tomography in Sarawak - Oon, Y.Y.; Khoo, S.I.; Mohd Amin, N.H.; Koh, K.T.; Khaw, C.S.; Shu, F.; Tan, C.T.; Voon, C.Y.; Khiew, N.Z.; Said, A.; Cham, Y.L.; Fong, A.Y.Y.; et al. (Elsevier, 2017)
Background: Coronary artery anomalies (CAAs) are rare. Some anomalies are associated with myocardial ischaemia, heart failure and sudden cardiac death. Objectives: The aims of this study were to determine the incidence of CAAs detected on multidetector computed tomography (MDCT) and their clinical relevance. Methods: We reviewed our center’s MDCT database from January 2005 to December 2015. Results: 76 out of 5677 (incidence 0.01%) patients were reported to have CAAs. They consisted of 44 patients (57.9%) with anomalous origin of right coronary artery (RCA), 7 (9.2%) with anomalous origin of left coronary artery (LCA), 3 (3.9%) with anomalous origin of the left circumflex artery (LCX), 1 (1.3%) with abnormal course of LCX, 15 (19.7%) with coronary artery fistulas, 3 (3.9%) with single coronary artery, 3 (3.9%) with anomalous left coronary artery from pulmonary artery (ALCAPA).We were able to retrieved 26 patients’ (mean age 49 ± 13 years, 17 male) case folder. They consisted of 11 patients with anomalous origin of the RCA (10 from left coronary sinus), 4 with anomalous origin of LCA from right coronary sinus (3 interarterial course), 7 with coronary fistulas (2 large fistulas), 1 with single coronary artery (Lipton LII, anterior course) , 3 with ALCAPA. Out of the 26 patients, 24 (92.3%) were alive and 2 were lost to follow-up. The commonest presenting symptom was chest pain (65.4%), followed by dyspnea (34.6%) and heart failure (11.5%). 3 patients underwent surgery and 1 underwent transcatheter coiling of fistula. 4 patients had positive functional test (2 anomalous origin of RCA, 1 anomalous origin of LCA from right coronary sinus and 1 ALCAPA). Only 1 patient who had positive functional test underwent surgery. The remaining 3 who did not undergo surgery were still alive. The patient with single coronary artery presented with heart failure and remained alive with pharmacotherapy. All 3 ALCAPA patients were alive, with the oldest patient survived to age 71 years. None of them had surgery performed. Conclusions: CAAs are rare. Majority of cases may be benign. Largescale studies are needed to better define the prognosis and optimal treatment of individual forms of CAAs.